Sentiment analysis of the coverage of the Tom Lembong corruption: Case in online media - Yuliarti, Astinana (Tamalanrea: Journal of Government and Development (JGD), 2025)
News coverage related to corruption is news that captures the public's attention, as is the case of the sugar import corruption case accused of the former Minister of Trade in the Jokowi era, Tom Lembong. The purpose of this study is to analysis sentiment on the news of Tom Lembong's corruption case in online media. The research method uses a descriptive qualitative approach with sentiment analysis techniques in online media with the Brand24 application. The data used are posts crawled from June 22 to July 22, 2025. The results showed that news related to the Tom Lembong case was dominated by the largest negative sentiment on July 19, 2025, the day after the 4.5-year sentence by the Corruption Court Judge against Tom Lembong. The accounts that have a large influence in influencing negative sentiment are the TikTok account of Inibukanniko and the YouTube account of warganet id, both of which have a perfect influence score of 10/10.